Becoming Rwandan : Education, Reconciliation, and the Making of a Post-Genocide Citizen. - Russell, S. Garnett (Genocide, Political Violence, Human Righ Ser., 2019)
In the aftermath of the genocide, the Rwandan government has attempted to use the education system in order to sustain peace and shape a new generation of Rwandans. Their hope is to create a generation focused on a unified and patriotic future rather than the ethnically divisive past. Yet, the government's efforts to manipulate global models around citizenship, human rights, and reconciliation to serve its national goals have had mixed results, with new tensions emerging across social groups. Becoming Rwandan argues that although the Rwandan government utilizes global discourses in national policy documents, the way in which teachers and students engage with these global models distorts the intention of the government, resulting in unintended consequences and undermining a sustainable peace.